2009
DOI: 10.1038/onc.2009.55
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine phosphorylase mRNA stability and protein levels are increased through ERK-mediated cytoplasmic accumulation of hnRNP K in nasopharyngeal carcinoma cells

Abstract: The cytoplasmic level of heterogeneous nuclear ribonucleoprotein K (hnRNP K) is significantly correlated with the elevated expression of thymidine phosphorylase (TP), and high levels of both proteins are predictive of a poor prognosis in nasopharyngeal carcinoma (NPC). We herein show that TP is highly induced by serum deprivation in NPC cells, and that this is due to an increase in the halflife of the TP mRNA, as shown by nuclear run-on and actinomycin D assays. We further show that the CU-rich element of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 32 publications
6
55
0
Order By: Relevance
“…In agreement with our observations about hnRNPs acetylation, one of the largest acetylome studies showed that the main functional networks modulated by acetylation were related to RNA maturation [35]. All in all, although the prominent role of hnRNPs in tumor progression has been already described [36][37][38], this is the first report showing a relation between KRAS mutational status and hnRNP acetylation. The highest level of acetyl-hnRNPs, and also the largest number of acetylated proteins, was found in cells harboring one single allele of KRAS G13D .…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our observations about hnRNPs acetylation, one of the largest acetylome studies showed that the main functional networks modulated by acetylation were related to RNA maturation [35]. All in all, although the prominent role of hnRNPs in tumor progression has been already described [36][37][38], this is the first report showing a relation between KRAS mutational status and hnRNP acetylation. The highest level of acetyl-hnRNPs, and also the largest number of acetylated proteins, was found in cells harboring one single allele of KRAS G13D .…”
Section: Discussionsupporting
confidence: 92%
“…In the tumor microenvironment, TNFa mediates cancer-related inflammation, and may promote tumor progression by increasing angiogenesis and metastasis. [1][2][3]25 The levels of TNFa [6][7] and its downstream genes c-FLIP 18,29 and thymidine phosphorylase [19][20][21][22] are known to be elevated in nasopharyngeal carcinoma tumor tissues. Here, we used Affymetrix chips to identify the 10 TNFa-inducible genes showing the highest upregulation in nasopharyngeal carcinoma tissues vs normal adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The primers used to amplify the GAPDH cDNA were as described previously. 22 Quantitative RT-PCR was performed on a Light-Cycler (Roche Diagnostics, Mannheim, Germany), according to the manufacturer's instructions, using the FastStart DNA Master SYBR Green I reagent (Roche Diagnostics). The gene expression results were normalized with regard to the expression of GADPH.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, cytoplasmic accumulation of hnRNP K through ERK-mediated phosphorylation of hnRNP K serines-284 and -353 has been reported in cervical carcinoma HeLa, 7 chronic myelogenous leukemia 8 and NPC 9 cells. The tumorigenic activity of hnRNP K appears to be conferred through its ability to increase proliferation, 10 antiapoptotic effects, 9 clonogenic potential 8 and metastasis. 11 These functions may be due, at least in part, to the ability of hnRNP K to upregulate the c-myc, 8,12 thymidine phosphorylase (TP) 9 and eIF4E 10 genes through transcriptional or post-transcriptional regulation.…”
mentioning
confidence: 99%